High-intensity exercise tolerance: An update on bioenergetics and assessment - Pettitt, R. W.; Clark, I. E. (Strength and Conditioning Journal, 2013)
The steady-state model of bioenergetics fails to accurately describe the metabolism for high-intensity power. This article reexamines the role of phosphocreatine, lactate production, and the importance of aerobic metabolism during short-term high-intensity power performance. Metabolic and mechanical tests of high-intensity power have evolved in the past 40 years. The authors compared the maximal accumulated oxygen-deficit model versus the critical power model and summarized the recently developed 3-minute all-out exercise test (3 mt). The 3 mt offers the strength and conditioning professional a simple method of estimating an athlete's tolerance to high-intensity power exercise.